2015
DOI: 10.1007/s11302-015-9443-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism for opioid dichotomy: bidirectional effect of μ-opioid receptors on P2X3 receptor currents in rat sensory neurones

Abstract: Here, we describe a molecular switch associated with opioid receptors-linked signalling cascades that provides a dual opioid control over P2X 3 purinoceptor in sensory neurones. Leu-enkephalin inhibited P2X 3 -mediated currents with IC 50~1 0 nM in~25 % of small nociceptive rat dorsal root ganglion (DRG) neurones. In contrast, in neurones pretreated with pertussis toxin leu-enkephalin produced stable and significant increase of P2X 3 currents. All effects of opioid were abolished by selective μ-opioid receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It is likely that deficits in dynorphin-enkephalin neuropeptide processing in the NAc of ENT1 –/– mice may play a role in dampening any ethanol-induced aversive effects, thus partly explaining the ability for this mouse model to excessively consume ethanol. More importantly, these findings provide further evidence supporting a relationship between deficits in ENT1 and adenosinergic signaling via the A 2A receptor, resulting in decreased enkephalin production in the striatum. , Other studies further support the adenosine-enkephalin relationship as adenosine A 1 and A 2A knockout mouse models of Parkinson’s and Huntington’s disease result in decreased striatal expression of pro-enkephalin and enkephalin mRNA. , Additional evidence strengthens the purinergic-enkephalin relationship in terms of nociception, given that Leu-Enkephalin inhibits P2X3-associated ion currents in rat dorsal root ganglion neurons . Thus, through our neuroproteomic investigation we are the first to report that alterations in adenosine signaling induced by deletion of ENT1 may mimic deficits in adenosine A 2A receptor function and produce deficits in PDYN–PCSK1–enkephalin signaling .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…It is likely that deficits in dynorphin-enkephalin neuropeptide processing in the NAc of ENT1 –/– mice may play a role in dampening any ethanol-induced aversive effects, thus partly explaining the ability for this mouse model to excessively consume ethanol. More importantly, these findings provide further evidence supporting a relationship between deficits in ENT1 and adenosinergic signaling via the A 2A receptor, resulting in decreased enkephalin production in the striatum. , Other studies further support the adenosine-enkephalin relationship as adenosine A 1 and A 2A knockout mouse models of Parkinson’s and Huntington’s disease result in decreased striatal expression of pro-enkephalin and enkephalin mRNA. , Additional evidence strengthens the purinergic-enkephalin relationship in terms of nociception, given that Leu-Enkephalin inhibits P2X3-associated ion currents in rat dorsal root ganglion neurons . Thus, through our neuroproteomic investigation we are the first to report that alterations in adenosine signaling induced by deletion of ENT1 may mimic deficits in adenosine A 2A receptor function and produce deficits in PDYN–PCSK1–enkephalin signaling .…”
Section: Discussionmentioning
confidence: 58%
“…39,40 Additional evidence strengthens the purinergic-enkephalin relationship in terms of nociception, given that Leu-Enkephalin inhibits P2X3-associated ion currents in rat dorsal root ganglion neurons. 41 Thus, through our neuroproteomic investigation we are the first to report that alterations in adenosine signaling induced by deletion of ENT1 may mimic deficits in adenosine A 2A receptor function and produce deficits in PDYN–PCSK1–enkephalin signaling. 20 Notably, human patients 42 and animal models exhibiting deficient PDYN activity and decreased enkephalin production demonstrate increased ethanol consumption 43 and cocaine-seeking behav-ior.…”
Section: Discussionmentioning
confidence: 89%
“…We have suggested a role of nociceptor calcium signaling in OIH (Araldi et al, 2018c). A MORindependent modulation of voltage-gated calcium channels and acid-sensing ion channels (ASICs) has also been implicated (Iegorova et al, 2010;Chizhmakov et al, 2015;Zaremba and Ruiz-Velasco, 2019). Lack of an in vitro model of OIH has made it difficult to study its underlying mechanisms at the cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that adenosine triphosphate (ATP)-gated cation channel P2X receptors are critical facilitators of cancer-related pain, and developing blockers against P2X receptors was a hotspot for treating cancer-related pain [105]. Opioids have been shown to be involved in the modulation of P2X receptors in sensory neurons [106]. Hence, the hypothesis that EMs function as analgesics in cancer-related pain by controlling P2X receptors needs to be further investigated.…”
Section: Involvement Of Ems In the Transmission And Modulation Of Noxmentioning
confidence: 99%